Magnetic Deformation Effect - O. V. Brodovyj, S. G. Bunchuk, V. G. Kolesnichenko, V. V. Skorokhod (Успехи физики металлов, 2001)
In a given paper, it is shown that, after the deformation by squeezing of single crystals of molybdenum and zinc, a sharp increase of magnetic susceptibility strongly depending on the surface state before deforming is observed. This phenomenon can be explained by ferromagnetism of electronic gas of ‘moderate density’. Conditions of contact friction on the boundary between metal and instrument influence on physical properties of the surface layer essentially. The chemical removal of this layer results in vanishing magnetic effect. The time dependence of ferromagnetic susceptibility component is determined, and it can be bound up with changing structure of the surface in the electric field.